Differentiation and activation of human CD4 T cells is associated with a gradual loss of myelin and lymphocyte protein. Issue 4 (25th January 2021) - Leitner, Judith; Mahasongkram, Kodchakorn; Schatzlmaier, Philipp; Pfisterer, Karin; Leksa, Vladimir; Pata, Supansa; Kasinrerk, Watchara; Stockinger, Hannes; Steinberger, Peter
Abstract: Upon generation of monoclonal antibodies to the T cell antigen receptor/CD3 (TCR/CD3) complex, we isolated mAb MT3, whose reactivity correlates inversely with the production of IFN‐γ by human peripheral blood T lymphocytes. Using eukaryotic expression cloning, we identified the MT3 antigen as myelin‐and‐lymphocyte (MAL) protein. Flow cytometry analysis demonstrates high surface expression of MAL on all naïve CD4 + T cells whereas MAL expression is diminished on central memory‐ and almost lost on effector memory T cells. MAL – T cells proliferate strongly in response to stimulation with CD3/CD28 antibodies, corroborating that MAL + T cells are naïve and MAL – T cells memory subtypes. Further, resting MAL – T cells harbor a larger pool of Ser59‐ and Tyr394‐ double phosphorylated lymphocyte‐specific kinase (Lck), which is rapidly increased upon in vitro restimulation. Previously, lack of MAL was reported to prevent transport of Lck, the key protein tyrosine kinase of TCR/CD3 signaling to the cell membrane, and to result in strongly impaired human T cell activation. Here, we show that knocking out MAL did not significantly affect Lck membrane localization and immune synapse recruitment, or transcriptional T cell activation. Collectively, our results indicate that loss of MAL is associated with activation‐induced differentiation of human T cells but not with impaired membrane localization of Lck or TCR signaling capacity. Abstract : Myelin‐and‐lymphocyte protein isoform‐A (MAL‐A) is highly expressed on human naive CD4 + T cells. Activation‐induced proliferation and differentiation is associated with a gradual loss of MAL expression, resulting in highly signalling‐competent effector‐memory cells with enhanced IFN‐γ‐secretion. Knockout of MAL does not affect recruitment of lymphocyte‐specific kinase Lck and TCR downstream signalling.